Amplified Fragment Length Polymorphism (AFLP) Based Genetic Diversity Studies in Betel Vine (Piper betle L.). Issue 2 (2nd October 2017) - Goyat, Shalini; Grewal, Anita; Hima Bindu, K.; Singh, Devendra; Katiyar, R.S.; Tewari, S.K.; Nainwal, Rakesh
ABSTRACT: Betel vine has been identified as an important cash crop in India. It is a vegetatively propagated plant and more than 100 landraces (cultivars) are cultivated in India. They are often named after the localities where they are grown. To assess the molecular genetic diversity among 10 betel vine cultivars, amplified fragment length polymorphism (AFLP) markers were used. Five AFLP primer combinations produced 323 bands of which 155 were polymorphic, leading to a 47.99% polymorphism. Average polymorphic information content (PIC) was 0.14 over all primer combinations. Genetic similarity was calculated from the Jaccard's similarity coefficient ( r ) value for all accessions which varied from 0.39 to 0.81, with an average of 0.60 implying a medium level of genetic variation between investigated cultivars. Cluster analysis divided the cultivars into two main clusters where M2 and M3 were closely related but F3 was separate from all others. The cluster analysis based on AFLP data indicated that cultivars were not grouped according to their geographic place of collection but rather by genetic relatedness. The principle coordinate analysis (PCA) of the markers was linked to the dendrograms generated by employing UPGMA.